Hubungan Pola Makan dengan Anemia Pada Ibu Hamil di Wilayah Kerja Puskesmas Kamonji Kota Palu - Enggar Enggar; Hasni Hasni; Fauziah Fauziah (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Anemia in pregnancy is a major health problem in developing countries with high morbidity rates in pregnant women. The average incidence of anemia in Asia is estimated at 72.6%. Pregnant women are one of the groups vulnerable to malnutrition, because there is an increase in nutritional needs to meet the needs of the mother and fetus. A good diet during pregnancy can help the body cope with the special demands of pregnancy, as well as having a positive influence on the baby's health. The aim of this research was to determine the relationship between diet and anemia in pregnant women at the Kamonji Community Health Center, Palu City. This research is a type of analytical research with a sample size of 69 pregnant women using purposive sampling techniques. Dietary pattern data was obtained using a questionnaire and hemoglobin level data using a digital measuring device (Easy Touch). Data analysis is univariate analysis using frequency distribution and bivariate analysis using the chi-square test. Based on the results of statistical tests using the chi-square test with a confidence level of 95% (α=0.05), it was found that X2 count was (1.8) and X2 table (3.841), that X2 count < X2 table, so Ho was accepted and Ha was rejected. And it can be concluded that there is no relationship between diet and anemia in pregnant women at Kamonji Health Center Working Area, Palu City.